Dialectics of Indonesian Culture and Malaysian Local Wisdom: Multicultural Learning Strategies at Sekolah Indonesia Kuala Lumpur - Tria Prella Rozanita; Muhammad Umair Khan Usman; Jaya Roza Azzukhrufi (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2026)
The operation of Indonesian schools abroad reflects broader tensions between national identity formation and the cultural forces shaping transnational education. Yet, insufficient attention has been given to how multicultural learning is negotiated in diaspora early childhood settings. This study interrogates the implementation of multicultural education at Sekolah Indonesia Kuala Lumpur (SIKL), examining the mechanisms by which teachers strategically integrate local Malaysian wisdom into the character formation of Indonesian kindergarten students while maintaining core national values. Employing a qualitative case study design, the research draws on participant observation of classroom routines, in-depth interviews with teachers, and systematic document analysis, with data interpreted through the interactive framework of Miles, Huberman, and Saldaña to capture processes of cultural mediation. The findings reveal a pedagogical formation conceptualized as blended habituation, in which teachers function as cultural brokers who mediate the dialectical relationship between Indonesian cultural values and Malaysian local wisdom, navigating nuanced sociocultural differences while enabling the coexistence of Indonesian moral frameworks with Malaysian public norms, such as disciplined queuing and regulated collective silence. These dynamics cultivate a functional hybrid identity aligned with the notion of Cross-Cultural Kids (CCKs), positioning transnational early childhood environments as formative sites for cosmopolitan nationalism and underscoring the imperative for diaspora curricula to move beyond preservation toward deliberate cultural accommodation in fostering adaptive competence.